Advances in accounting education. Volume 21, - Rupert, Timothy J.; Kern, Beth Burchfield, 1958- (Emerald Publishing Limited, 2017)
Advances in Accounting Education: Teaching and Curriculum Innovations publishes both non-empirical and empirical articles dealing with accounting pedagogy. All articles explain how teaching methods or curricula/programs can be improved. Non-empirical papers are academically rigorous, and specifically discuss the institutional context of a course or program, as well as any relevant tradeoffs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review, including references from outside the accounting field, where appropriate. Volume 21 includes papers that examine the following topics: a commentary and analysis of the new CPA exam, a citation analysis of Advances in Accounting Education for volumes 1-15, and an application of methods for reducing writing apprehension in students. The volume also includes a special section that focuses on active learning. One article presents a series of active learning assignments for use in introductory financial accounting classes while the other manuscript presents the results of a survey of accounting faculty and their incorporation of active learning techniques in their classes
Obsahuje index.
Keywords: Accounting -- Study and teaching (Higher); Educational innovations.; elektronické knihy; electronic books